ddRADseq-assisted construction of a high-density SNP genetic map and QTL fine mapping for growth-related traits in the spotted scat (Scatophagus argus) - Wei Yang; Yaorong Wang; Dongneng Jiang; Changxu Tian; Chunhua Zhu; Guangli Li; Huapu Chen (BMC Genomics, 2020)
Abstract Background Scatophagus argus is a popular farmed fish in several countries of Southeast Asia, including China. Although S. argus has a highly promising economic value, a significant lag of breeding research severely obstructs the sustainable development of aquaculture industry. As one of the most important economic traits, growth traits are controlled by multiple gene loci called quantitative trait loci (QTLs). It is urgently needed to launch a marker assisted selection (MAS) breeding program to improve growth and other pivotal traits. Thus a high-density genetic linkage map is necessary for the fine mapping of QTLs associated with target traits. Results Using restriction site-associated DNA sequencing, 6196 single nucleotide polymorphism (SNP) markers were developed from a full-sib mapping population for genetic map construction. A total of 6193 SNPs were grouped into 24 linkage groups (LGs), and the total length reached 2191.65 cM with an average marker interval of 0.35 cM. Comparative genome mapping revealed 23 one-to-one and 1 one-to-two syntenic relationships between S. argus LGs and Larimichthys crocea chromosomes. Based on the high-quality linkage map, a total of 44 QTLs associated with growth-related traits were identified on 11 LGs. Of which, 19 significant QTLs for body weight were detected on 9 LGs, explaining 8.8–19.6% of phenotypic variances. Within genomic regions flanking the SNP markers in QTL intervals, we predicted 15 candidate genes showing potential relationships with growth, such as Hbp1, Vgll4 and Pim3, which merit further functional exploration. Conclusions The first SNP genetic map with a fine resolution of 0.35 cM for S. argus has been developed, which shows a high level of syntenic relationship with L. crocea genomes. This map can provide valuable information for future genetic, genomic and evolutionary studies. The QTLs and SNP markers significantly associated with growth-related traits will act as useful tools in gene mapping, map-based cloning and MAS breeding to speed up the genetic improvement in important traits of S. argus. The interesting candidate genes are promising for further investigations and have the potential to provide deeper insights into growth regulation in the future.